SARESP - Sistema de Avaliação do Rendimento Escolar do estado de São Paulo: repercussão do resultado positivo em duas escolas no ano de 2007 - Chiste, Mônica Cristina (2009)
The application of evaluations of the public teaching grew in Brazil starting from the last decades of the century XX, in face of the need of changes in the Education. In order to obtain resources rulers resorted to the World Bank proposed that the presentation of projects aimed at improving the quality of education. Thus arose the need to check the efficiency of the restructuring of teacher education through the application of evaluations of school performance. Initially the focus was the assessment of learning and now come the performance evaluations of teachers, courses, institutions and the educational system. Endeavoring to build a political assessment of the educational system in the State of Sao Paulo, the government established the Program for Educational Evaluation of the State Network and from 1996 there is the System Evaluation Educational Achievement of Sao Paulo - SARESP, which summarizes the evaluation of performance of students of elementary and high schools. In this context, this study aims to identify factors and educational activities carried out in two schools that received top scores in mathematics in the Report of SARESP/2007. Data collection was based on reflective interviews with the managers, directors and coordinators of two schools in the southern city of Sao Paulo, as well as observations made in these two schools and reported in research journals, in documents made available by schools and school performance reports for the SARESP/2007 provided by the state government on the Internet. This research revealed that some factors and actions that contribute to the good performance of these schools: effective group of teachers working in schools for many years and so cohesive; search for results that reflect the efforts of teachers and students, meetings with teachers and administrators to re - and discuss teaching strategies, directors and coordinators active, serving as a liaison between students and desires of the community and the school